Visionary Art of the Americas: Hemispheric Transculturations, Hallucinogens, Politics, Aesthetics, and Mass Consumer Culture in the United States, Mexico, and Colombia - Cadena Botero, Juan David (Lexington Books, 2023)
Unlike their European predecessors, many Latin American and North American authors turned to hallucinatory substances as elements of their own hemispheric heritage. The twentieth-century narratives analyzed in Visionary Art of the Americas: Hemispheric Transculturations, Hallucinogens, Politics, Aesthetics, and Mass Consumer Culture in the United States, Mexico, and Colombia acquire their true depth only within a much wider realm of visionary traditions spanning Asia, Africa, and the Americas. Socially and culturally marginalized alongside users, hallucinogens—simultaneously a colonial anathema and a sacred pre-Columbian ritual—have gained increased mainstream acceptance. The various films and texts analyzed in this book attest to the true heterogeneity of hallucinogenic experience in the Americas at a time when scholarly attention to hallucination and visions as a survival adaptation of organic intelligence is crucial to understand its differences from A.I.